Wage-setting behavior in France: additional evidence from an ad-hoc survey - Jérémi Montornès; Jacques-Bernard Sauner-Leroy (European Central Bank (ECB), 2009)
We investigate the wage-setting behavior of French companies using an ad-hoc survey conducted specifically for this study. Our main results are the following. i) Wages are changed infrequently. The mean duration of wage contracts is one year. Wage changes occur at regular intervals during the year and are concentrated in January and July. ii) We find a lower degree of down-ward real wage rigidity and nominal wage rigidity in France compared to the European average. iii) About one third of companies have an internal policy to grant wage increases according to inflation. iv) When companies are faced adverse shocks, only a partial response is transmitted into prices. Companies also adopt cost-cutting strategies. The wage of newly hired employees plays an important role in this adjustment.
Keywords: E3; D4; L11; 330; survey data; wage rigidity; wage-setting behavior; Lohnrigidität; Lohnbildung; Frankreich